Probabilistic Reasoning in the Sciences (The Reasoner, 2025)
Report on the Conference on Probabilistic Reasoning in the Sciences which took place at the  Marche Polytechnic University in Ancona, Italy. 29-31 August 2024.
Keywords: Probabilistic reasoning; Science; Methodology